Tortuga in trouble - Paul, Ann Whitford; Long, Ethan (New York : Holiday House, 2009)
Tortuga arrives at his grandmother's house to bring her supper and is alarmed to find her looking suspiciously like Coyote. Includes a glossary of Spanish words.
2.1
K-3
Text mainly in English with some words in Spanish.
Keywords: Desert animals -- Juvenile fiction; Grandmothers -- Juvenile fiction; Turtles -- Juvenile fiction; Desert animals -- Fiction; Grandmothers -- Fiction; Turtles -- Fiction; Desert animals -- Fiction; Grandmothers -- Fiction; Turtles -- Fiction